2016
DOI: 10.1177/1071100716629778
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Surgical Management of Achilles Tendon Sleeve Avulsions

Abstract: Level IV, retrospective case series.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 31 publications
(35 reference statements)
8
29
0
Order By: Relevance
“…All 11 patients in our series met the criterion of being overweight or obese. Similar findings were reported by Huh [12]. To reduce the risk of Achilles sleeve avulsion, we suggest weight loss and health education for overweight patients who have presented tendinopathy symptoms.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…All 11 patients in our series met the criterion of being overweight or obese. Similar findings were reported by Huh [12]. To reduce the risk of Achilles sleeve avulsion, we suggest weight loss and health education for overweight patients who have presented tendinopathy symptoms.…”
Section: Discussionsupporting
confidence: 89%
“…According to unpublished data from our institution collected over the previous 5 years, Achilles sleeve avulsion only constituted 2.6% of all Achilles tendon ruptures. A previous study reported that Achilles sleeve avulsion typically arose from insertional Achilles tendinopathy [11,12]. We also observed a high prevalence (11 of 11 cases) of pre-existing insertional Achilles tendinopathy in our series.…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations